《等级标准》与印尼本土中文师资培训以培养“中文+职业技能”课程的结合 - Stephanie Phanata (Sinolingua: Journal of Chinese Studies, 2024)
In recent years, the “Chinese Proficiency Grading Standards for International Chinese Language Education” (hereinafter referred to as “Grading Standards”) have attracted worldwide attention for improving the quality of Chinese teaching. However, local Chinese teacher training in Indonesia rarely discusses the role of “Grading Standards”. Many local professional Chinese teachers in universities do not understand how to combine “Grading Standards” with “Chinese + Vocational Skills” courses. This article explains the “Grading Standards” and the methods and directions of local Chinese teacher training in Indonesia. First, we will introduce the requirements and types of “Chinese + Vocational Skills” courses for Chinese language majors in vocational colleges in Indonesia. Secondly, it proposes training content for local Chinese teachers in Indonesia. The final article provides the “Grading Standards” and Indonesian local Chinese teacher training methods based on constructivist theory. The author hopes that it will be helpful to promote the sustainable development of Chinese teacher training in Indonesia and achieve the goals of Chinese teaching.